Emergency Reasons in Marriage Dispensation (Legal Norms) : A Case Study in Bawean Island, Indonesia - Muhammad Zulfi Al'Ghani; Badrizal Al Hazar; Ease Arent; Muhammad Nur Hidayat; Ramadhani Lausi Mkumbachi (Universitas Negeri Gorontalo, 2025)
Early marriages in various countries, including Indonesia, can be legalized by the state based on